Comprehensive analysis of the potential mechanism of gansui in blocking non-small cell lung cancer progression - Yang, Xiaoxu; Li, Wenlan (Pharmaceutical biology, 2025)
Gansui [ T. N. Liou ex S.B.Ho (Euphorbiaceae)] has been reported to inhibit the proliferation of non-small cell lung cancer (NSCLC) cells; however, its underlying pharmacological mechanism remains unclear. To investigate the potential effects and mechanisms of Gansui in blocking NSCLC progression. The targets of Gansui's components and NSCLC-related targets were obtained through public database and published studies. Functional enrichment analysis was performed using the clusterProfiler R package. STRING database was used for protein-protein interaction analysis. CytoHubba plugin was applied to get the hub genes. Molecular docking was applied to assess the binding affinities between the hub targets and the crucial components. Kidjolanin was used to treat A549 and NCI-H1385, and its effects on cell viability, sensitivity of paclitaxel and expression levels of hub genes were investigated by cell counting kit-8 assay, flow cytometry and qPCR. A total of 16 Gansui active ingredients and 337 targets were collected, of which 298 targets overlapped with NSCLC-related genes. , , , and were identified as hub genes. The components in Gansui, including kidjoranin 3-O-β-digitoxopyranoside, cynotophylloside B, 13-Oxyingenol-dodecanoate, and kidjolanin had good binding affinity with the hub targets. Kidjolanin inhibited the viability of NSCLC cells, promoted apoptosis and inhibited the expression of hub genes. Kidjolanin also enhanced the proliferation inhibition and apoptosis of NSCLC cells induced by paclitaxel. Gansui exerts anti-NSCLC effects multiple downstream targets, implying its potential in NSCLC treatment.